2018
DOI: 10.1148/radiol.2018172888
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy and Surgery for Breast Cancer: Preoperative MRI Features Associated with Local Recurrence

Abstract: Purpose To investigate the MRI and clinical-pathologic features associated with local-regional recurrence (LRR) in patients who had undergone breast-conserving surgery (BCS) following neoadjuvant chemotherapy (NAC). Materials and Methods In this retrospective, single-institution study between October 2003 and September 2015, 548 consecutive women, consisting of 468 down-staged and 80 preplanned BCS patients (mean age, 45.7 years; range, 22-75 years), underwent preoperative MRI and BCS following NAC. The rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…Presurgical assessment after NAC to assess the potential of BCS.-BCS following NAC is considered safe because no significant difference has been found in local recurrence rates between a BCS group and a mastectomy group or between a downstaged BCS group and a preplanned BCS group (140,141). An age of younger than 40 years is associated with a higher rate of local recurrence (142). MRI can guide BCS following NAC, although it has not been proven that preoperative MRI is associated with improved surgical outcomes or recurrence rates (143).…”
Section: Evaluation Of Women Treated With Neoadjuvant Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Presurgical assessment after NAC to assess the potential of BCS.-BCS following NAC is considered safe because no significant difference has been found in local recurrence rates between a BCS group and a mastectomy group or between a downstaged BCS group and a preplanned BCS group (140,141). An age of younger than 40 years is associated with a higher rate of local recurrence (142). MRI can guide BCS following NAC, although it has not been proven that preoperative MRI is associated with improved surgical outcomes or recurrence rates (143).…”
Section: Evaluation Of Women Treated With Neoadjuvant Chemotherapymentioning
confidence: 99%
“…These results can be explained by the fact that hormone receptor-positive/HER2-negative tumors more frequently manifest as diffuse NME and reduce into multiple small foci following chemotherapy (147). The presence of NME at preoperative MRI is also associated with worse local-regional recurrence-free survival in patients who underwent BCS after NAC (142), with recurrences usually manifesting in the same quadrant as the original tumor.…”
Section: Evaluation Of Women Treated With Neoadjuvant Chemotherapymentioning
confidence: 99%
“…The present study found a higher recurrence rate among patients aged 50 years or older, compared to younger age groups, 37.5% Vs. 7.5%, respectively, Conversely, Shin et al From the Republic of Korea, reported in 2018 that the younger age ≤ 40 years were associated with worse recurrence. (Sweeting et al, 2011;Shin et al, 2018). It is recognized that NAC can effectively downstage the main neoplasm.…”
Section: Resultsmentioning
confidence: 99%
“…Tumors with higher cellularity usually present as masses, whereas scattered tumor cells and tumors with lower cellularity present as NME, which may underlie the association between NME and resection margin status ( 33 ). Among the enhancing patterns of ILC on MRI, NME has been correlated with malignant cells streaming in a single-file fashion in the breast stroma or small tumor aggregates separated by normal tissue, which would likely cause underestimation of tumor extent ( 34 35 ). Our results are also consistent with previous studies, which have reported that NME lesions show higher discordance than mass lesions in estimating tumor size ( 36 ).…”
Section: Discussionmentioning
confidence: 99%